The validity and reliability of the exposure index as a metric for estimating the radiation dose to the patient - Erenstein, H.G.; Browne, D.; Curtin, S.; Dwyer, R.S.; Higgins, R.N.; Hommel, S.F.; Menzinga, J.; Pires Jorge, J.A.; Sauty, M.; de Vries, G.; England, A. (Radiography (London, England. 1995), 2020)
With the introduction of digital radiography, the feedback between image quality and over-exposure has been partly lost which in some cases has led to a steady increase in dose. Over the years the introduction of exposure index (EI) has been used to resolve this phenomenon referred to as ‘dose creep’. Even though EI is often vendor specific it is always a related of the radiation exposure to the detector. Due to the nature of this relationship EI can also be used as a patient dose indicator, however this is not widely investigated in literature. A total of 420 dose-area-product (DAP) and EI measurements were taken whilst varying kVp, mAs and body habitus on two different anthropomorphic phantoms (pelvis and chest). Using linear regression, the correlation between EI and DAP were examined. Additionally, two separate region of interest (ROI) placements/per phantom where examined in order to research any effect on EI. When dividing the data into subsets, a strong correlation between EI and DAP was shown with all R-squared values > 0.987. Comparison between the ROI placements showed a significant difference between EIs for both placements. This research shows a clear relationship between EI and radiation dose which is dependent on a wide variety of factors such as ROI placement, body habitus. In addition, pathology and manufacturer specific EI’s are likely to be of influence as well. The combination of DAP and EI might be used as a patient dose indicator. However, the influencing factors as mentioned in the conclusion should be considered and examined before implementation.